An analysis of the adequacy of the library collection to the studio arts programs of the College of Fine Arts - Robles, Lissette R. (Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The study focused on answering if the College of fine Arts Library collection is adequate in providing the information needs of the students under the Department of Studio Arts. Two evaluation schemes were utilized in the study: collection-centered and use-centered evaluation. A comparison against the existing PAARL standards was used as the collection-centered parameter. The amount of book collection under the college library's safe keeping was weighed against the 5,000 titles plus additional 5 titles per student book requirement. Review of book loans made for the past three years (2001-2003) served as the use-centered evaluation resources. Subject areas frequently borrowed during this period of time were analyzed.